Adaptation of the Educational Motivation Scale Into a Short Form With Multigroup Analysis in a Vocational Training and Baccalaureate Setting - Expósito-López, Jorge; Romero-Díaz de la Guardia, José Javier; Olmedo-Moreno, Eva María; Pistón Rodríguez, María Dolores; Chacón-Cuberos, Ramón (Frontiers in Psychology, 2021)
The aim of the present study was to adapt the educational motivation scale into an abbreviated version (EMS-SF), in addition to analysing its psychometric properties for use with vocational training (FP) and baccalaureate students using structural equations. A cross-sectional and ex post facto study was conducted with a sample of 1159 students from the autonomous community of Andalusia (Spain). IBM SPSS® and IBM AMOS® software programs were used for data analysis. With regards to main outcomes, the scale reflected good fit indices in its short form, presenting a more parsimonious and easily understood questionnaire. The questionnaire was reduced from a total of 28 to 19 items. In the same way, the number of dimensions was reduced from seven to four, facilitating scale understanding and interpretation according to self-determination theory. As a main finding, it was observed that the most relevant items for baccalaureate students pertained to the pleasure derived from discovering things and to overcoming challenges, whereas in FP students, items pertaining to the satisfaction generated from exerting effort, achieving one’s best and being well paid were more relevant. In conclusion, findings urge the need to strengthen intrinsic motivation in FP students with the aim of avoiding demotivation and poor academic performance.